Chemical Weathering of the Mekong River Basin With Implication for East Asian Monsoon Evolution During the Late Quaternary: Marine Sediment Records in the Southern South China Sea - Sang, Pham Nhu; Liu, Zhifei; Colin, Christophe (Frontiers in Earth Science, 2022)
Clay mineralogy, major-element geochemistry, and Sr-Nd isotopic compositions from Core MD05-2896 collected in the southern South China Sea have been utilized to investigate discrimination of sediment provenance and to reconstruct a history of chemical weathering in the Mekong River basin over the last 45 ka. The results display that the clay mineral assemblage of the core is characterized by abundant smectite (27–56%) and illite (18–32%), with moderate kaolinite (13–23%) and chlorite (11–18%), and the 87Sr/86Sr ratio and εNd value narrowly vary in the ranges of 0.7232 to 0.7272 and from –10.9 to –9.6, respectively. According to clay mineralogy and Sr-Nd isotopic compositions, the Mekong River is the main terrigenous sedimentary source to the southern South China Sea, with no detectable change over the time span of the study, despite strong sea-level fluctuations. Clay mineralogy and elemental geochemistry analyses reveal that higher smectite/(illite + chlorite), smectite/kaolinite, TiO2/K2O, and SiO2/K2O ratios during the Marine Isotope Stage (MIS) 3 and 1 suggest enhanced chemical weathering, while lower values of these ratios during MIS 2 indicate weakened chemical weathering. These proxies reveal a close relationship with the available climate records of the East Asian monsoon evolution, implying that the chemical weathering in the Mekong River basin has been strongly controlled by the East Asian monsoon rainfall.